How Do Word-of-Mouth Reviews Affect Product Sales? Applying the Stock Market Analogy to Online Stores - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2007)
Online word-of-mouth communication -- such as product reviews by consumers -- has become a major information source about product quality. Singapore Management University information systems professor Nan Hu and his team investigated both quantitative and qualitative aspects of online reviews using Amazon.com as their study base. They found that, besides review scores, consumers do pay attention to other contextual information such as a reviewer’s reputation and exposure. Hu’s research also showed that the longer an item is on the market, the smaller the impact of online reviews on sales.